Neurodiversity, Giftedness, and Aesthetic Perceptual Judgment of Music in Children with Autism - Masataka, Nobuo (Frontiers in Psychology, 2017)
The author investigated the capability of aesthetic perceptual judgment of music in male children diagnosed with autism spectrum disorder (ASD) when compared to age-matched typically developing (TD) male children. Nineteen boys between 4 and 7 years of age with ASD were compared to 28 TD boys while listening to musical stimuli of different aesthetic levels. The results from two musical experiments using the above participants, are described here. In the first study, responses to a Mozart minuet and a dissonant altered version of the same Mozart minuet were compared. In this first study, the results indicated that both ASD and TD males preferred listening to the original consonant version of the minuet over the altered dissonant version. With the same participants, the second experiment included musical stimuli from four renowned composers: Mozart and Bach’s musical works, both considered consonant in their harmonic structure, were compared with music from Schoenberg and Albinoni, two composers who wrote musical works considered exceedingly harmonically dissonant. In the second study, when the stimuli included consonant or dissonant musical stimuli from different composers, the children with ASD showed greater preference for the aesthetic quality of the highly dissonant music compared to the TD children. While children in both of the groups listened to the consonant stimuli of Mozart and Bach music for the same amount of time, the children with ASD listened to the dissonant music of Schoenberg and Albinoni longer than the TD children. As preferring dissonant music is more aesthetically demanding perceptually, these results suggest that ASD male children demonstrate an enhanced capability of aesthetic judgment of music. Subsidiary data collected after the completion of the experiment revealed that absolute pitch ability was prevalent only in the children with ASD, some of whom also possessed extraordinary musical memory. The implications of these results are discussed with reference to the broader notion of neurodiversity, a term coined to capture potentially gifted qualities in individuals diagnosed with ASD.